2004
DOI: 10.1097/00004872-200405000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term intake of edible oils on hypertension and myocardial and aortic remodelling in spontaneously hypertensive rats

Abstract: The most beneficial cardiac and aortic structural effects occurred in the fish-oil group. Both canola oil and palm oil were also effective in reducing blood pressure, favouring myocardial remodelling, although they produced contrasting effects with regard to aorta wall structure. Soybean oil and olive oil had mild effects on myocardial and aortic structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…In this work control of blood pressure by OV in treated hypertensive group has markedly delayed and slightly improved the histological changes that appeared in untreated hypertensive rats which coincided with Eddouks [29] who have demonstrated the importance of intensive BP control preferably systolic BP less than 130 mmHg to delay progression of renal disease in hypertension and diabetes. The significant drop of systolic BP in treated hypertensive rats with OV as shown in this study agreed and fully explained by Engler [30] and Aguila [31] who reported that OV reduced the BP by reduction of vascular reactivity to noradrenaline blunting the rennin-angiotensinaldosterone system by decreasing adrenal synthesis of aldosterone.…”
Section: Caspase-3 Expressionsupporting
confidence: 90%
“…In this work control of blood pressure by OV in treated hypertensive group has markedly delayed and slightly improved the histological changes that appeared in untreated hypertensive rats which coincided with Eddouks [29] who have demonstrated the importance of intensive BP control preferably systolic BP less than 130 mmHg to delay progression of renal disease in hypertension and diabetes. The significant drop of systolic BP in treated hypertensive rats with OV as shown in this study agreed and fully explained by Engler [30] and Aguila [31] who reported that OV reduced the BP by reduction of vascular reactivity to noradrenaline blunting the rennin-angiotensinaldosterone system by decreasing adrenal synthesis of aldosterone.…”
Section: Caspase-3 Expressionsupporting
confidence: 90%
“…Some animal studies have assessed its effect on BP. In general, the results do not show an important beneficial effect of this vegetable oil on BP 38,39 . On the contrary, rats fed diets rich in canola oil lived a shorter time than rats fed with PUFA-enriched diets 40,41 .…”
Section: Feeding Trialsmentioning
confidence: 56%
“…The plant was also reported to possess anti-inflammatory (Ocana-Fuentes et al, 2010) and antimicrobial (Sarac and Ugur, 2008) activities, which could also be supplementing its beneficial effect, as the infection and inflammation are likely to be associated with urolithiasis process. A few studies on the effectiveness of herbal remedies in urolithiasis exists, such as Hernaira hirsute, phylanthusniruri and Hibiscus sabdariffa, which showed promising results in the management of urolithiasis (Aguila et al, 2004;Butterweck and Khan, 2009;Chishti et al, 2013).…”
Section: Discussionmentioning
confidence: 99%